1999
DOI: 10.1097/00002030-199909100-00009
|View full text |Cite
|
Sign up to set email alerts
|

A syndrome of peripheral fat wasting (lipodystrophy) in patients receiving long-term nucleoside analogue therapy

Abstract: Lipodystrophy may be related to long-term NRTI therapy, particularly that including stavudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
246
2
21

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(283 citation statements)
references
References 12 publications
13
246
2
21
Order By: Relevance
“…In our study, we confirmed the strong effects of longer d4T use, but not AZT, on the development of lipoatrophy in HIV-infected Koreans, supporting several prior reports per- formed in various populations (Saint-Marc et al 1999;Wohl et al 2006;van Griensven et al 2007;Waters and Nelson 2007;Brown 2008). In general, lipoatrophy is clearly linked with HAART, and is especially strongly associated with the use of d4T, and is more likely to improve upon treatment regimen change (Grinspoon and Carr 2005;Pujari et al 2005;van Griensven et al 2007;Waters and Nelson 2007;Wierzbicki et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we confirmed the strong effects of longer d4T use, but not AZT, on the development of lipoatrophy in HIV-infected Koreans, supporting several prior reports per- formed in various populations (Saint-Marc et al 1999;Wohl et al 2006;van Griensven et al 2007;Waters and Nelson 2007;Brown 2008). In general, lipoatrophy is clearly linked with HAART, and is especially strongly associated with the use of d4T, and is more likely to improve upon treatment regimen change (Grinspoon and Carr 2005;Pujari et al 2005;van Griensven et al 2007;Waters and Nelson 2007;Wierzbicki et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Localized fat atrophies in the cheeks, similar to those seen in facial lipodystrophy after HIV treatment [11,57], occurred 2-3 months after the implantation of Restylane or New-Fill in the nasolabial folds of healthy patients. At 9 months, the implants could still be identified and were interspersed with giant cells and granulomatous tissue.…”
Section: Complicationsmentioning
confidence: 80%
“…These substances are useful for the correction of congenital or traumatic facial, bony, and soft tissue defects [10], and in patients suffering from scleroderma, Romberg's disease, facial wasting, or lipodystrophy following AIDS treatment [2,11,57]. Additional indications are unilateral paralysis of vocal cords [12,24,28], augmentation of the lip and soft palate in cleft lip patients, anophthalmic orbits [10], or enophthalmus.…”
mentioning
confidence: 99%
“…Moreover, the lactic acidosis/hepatic steatosis syndrome may be more common than previously appreciated in adults (Boubaker et al, 2000;Lonergan et al, 2000;Ter Hofstede et al, 2000) and children (Church et al, 2000) treated with NRTIs. d4T treatment causes lipodystrophy (Saint-Marc et al, 1999). Mechanisms may involve altered mitochondrial biogenesis and/or oxidative changes and possibly adipocyte apoptosis (Harrison, 1997;Lewis and Dalakas, 1995).…”
Section: Toxicity From Other Nrtis: Varying Tissue Targetsmentioning
confidence: 99%